2019
DOI: 10.3390/molecules24132446
|View full text |Cite
|
Sign up to set email alerts
|

New HSV-1 Anti-Viral 1′-Homocarbocyclic Nucleoside Analogs with an Optically Active Substituted Bicyclo[2.2.1]Heptane Fragment as a Glycoside Moiety

Abstract: New 1′-homocarbanucleoside analogs with an optically active substituted bicyclo[2.2.1]heptane skeleton as sugar moiety were synthesized. The pyrimidine analogs with uracil, 5-fluorouracil, thymine and cytosine and key intermediate with 6-chloropurine (5) as nucleobases were synthesized by a selective Mitsunobu reaction on the primary hydroxymethyl group in the presence of 5-endo-hydroxyl group. Adenine and 6-substituted adenine homonucleosides were obtained by the substitution of the 6-chlorine atom of the key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The docking score (PLANTPLP score) is a function described in Korb et al [20]. "For a strong binding, the score has a negative value; for weak or non-existing binding, the score has a less negative or even positive value" [21]. https://doi.org /10.37358/Rev.…”
Section: Resultsmentioning
confidence: 99%
“…The docking score (PLANTPLP score) is a function described in Korb et al [20]. "For a strong binding, the score has a negative value; for weak or non-existing binding, the score has a less negative or even positive value" [21]. https://doi.org /10.37358/Rev.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the primary alcohol reacted selectively to give the key nucleoside intermediate 5G isolated by simple crystallization in 71.3 % yield (Scheme 1). For comparison, 6chloropurine reacted with diol 2 in the same Mitsunobu reaction in 67.6 % yield [4,5].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, D-6′-fluorinated-aristeromycin analogs (Figure 3) were designed to assess the inhibition of the human SAH and correlate the potential antiviral activity against CHIKV by a probable inhibition of nsP1. It was found that the 6-amino-purines (24,25,26) showed interesting results for SAH inhibition or for anti-CHIKV activity when compared with aristeromycin and also with other purines (27 and 28), pyrimidines (29)(30)(31)(32)(33), and phosphoramidates (34,35,36) as summarized in Table 2. These data confirmed the antiviral activity against CHIKV and also suggested that the observed activity may be due to an indirect effect on the activity of nsP1.…”
Section: Aristeromycin Analogsmentioning
confidence: 99%
“…Moreover, this class of molecules is usually reported as being druggable and safe for human use, which makes it more attractive for further development. Therefore, in the present review, we will summarize natural and synthetic nitrogen-based heterocyclics and their derivatives with reported anti-CHIKV activity [ 9 , 11 , 19 , 25 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and explore the potential of these molecules as an interesting class for antiviral drug development.…”
Section: Overview Of Chikv Drugs and The Versatility Of Nitrogen-bmentioning
confidence: 99%